Fundamentals of fluid mechanics - Munson, Bruce Roy, 1940-; Okiishi, T. H. (Theodore Hisao), 1939-; Huebsch, Wade W.; Rothmayer, Alric P., 1959-. (Hoboken, NJ : John Wiley & Sons, Inc., 2013)
'Fundamentals of Fluid Mechanics offers comprehensive topical coverage, with varied examples and problems, application of visual component of fluid mechanics, and strong focus on effective learning. The text enables the gradual development of confidence in problem solving. Each important concept is introduced in easy-to-understand terms before more complicated examples are discussed. Continuing this book's tradition of extensive real-world applications, this latest edition includes more Fluid in the News case study boxes in each chapter, new problem types, an increased number of real-world photos, and additional videos to augment the text material and help generate interest in the topic. Example problems have been updated and numerous new photographs, figures, and graphs have been included. In addition, there are 150 videos designed to aid and enhance comprehension, support visualization skill building and engage users more deeply with the material and concepts'--
Includes bibliographical references and index.
Keywords: Fluid mechanics -- Textbooks